New Lobellini (Collembola: Neanuridae) from Queensland contribute to understanding distribution and ecology of Australian fauna. Issue 2 (28th May 2020) - Smolis, Adrian; Greenslade, Penelope
Abstract: Two new species from Queensland rainforest belonging to genera Hemilobella and Sphaeronura are described and illustrated with drawings and colour photographs. Hemilobella matildae sp. nov. Smolis and Greenslade is characterised by elongated tubercles laterally on body and an elongated ogival labrum. Sphaeronura ameliae sp. nov. Smolis and Greenslade differs from other taxa in the genus in chaetotaxic features and the presence of a male ventral organ. A new record of Australonura scoparia is included. The high species richness of lowland rainforests, in which these log inhabiting saproxylic species were found, is noted, and the contribution that extreme events such as cyclones in maintaining the fallen timber habitat is emphasised. The bright colour of these species may be caused by sequestered pigments from the slime moulds on which they feed. The colour probably also acts as a warning to predators that individuals are distasteful. A description of the distributions, characteristics, distinctiveness and possible genesis of Australian fauna of the subfamily Neanurinae is presented, and a checklist of species and key to all Australian genera of the subfamily is included. Species in this subfamily are predominately short‐range endemics so should be surveyed whenever wet forests are under threat from logging or urban expansion.